Preliminary Study - Analytical Approach in Experimental Rig of Automotive Flexible Wiper System - Salim, Mohd Azli; Abdul Munir, Fudhail; Razali, Nadlene; Mat Nuri, Nur Rashid; Mohamad Zin, Mohd Rody (ICOCI Publisher, 2011)
In this study, experimental rig of automotive wiper System is designed and analyzed using numerical tool. Generally, this rig utilizes different types of electric motor as a power assist. In addition, a suitable dimension and material for each part was chose for the rig. There are two main considerations in order to design the experimental rig. The first consideration is the selection of power assist (electric motor) and the second is the consideration made pertaining to the criteria the design method. In research methodology, the design and materials used in this study is needed to be structurally analyzed using analytical calculation. After the calculation is complete and the desired results is obtained, then only the experimental rig of automotive wiper system can be fabricated and tested. The platform of the rig was analyzed to identify the external forces acting on the rig. Structural finite element analysis is conducted on the completed a best design. It is to ensure the rig has a safety factor during the experiment going on.